Udigrudi recifense e suas performances - Patury, Fernando Fagner (2023)
The purpose of this dissertation is to analyze the Udigrudi Recifense counterculture movement, which emerged at the beginning of the 1970s. A movement initiated through cultural hybridism and reaction to the social and political context of the Military Dictatorship. Thus, we are willing to discuss counterculture and movements prior to Udigrudi and the situation of Brazilian culture and artists during a period of political change and tension. Through the perspective of cultural performances, the work is dedicated to exposing the main aesthetic elements of this movement, from its emergence, environments, productions and impacts on Brazilian culture and arts. Methodologically, we will use the review of bibliographies on the topic and analysis of Udigrudi's diverse artistic productions. We will rely on the influence of history, sociology, geography and other areas of human sciences to expose existing contrasts between the Udigrudi Movement and the historical context in which it was inserted. The stabilization of ideals and ideologies is built in culture through various mechanisms. Within each social, historical and political context, there is a construction of practices, knowledge and living that are rooted through practices and disseminated through communication and cultural vehicles. Likewise, ideas, movements and manifestations arise that oppose this mass culture.